Experimental investigation for the solubility and micronization of pyridin-4-amine in supercritical carbon dioxide. (March 2017) - Chen, Chun-Ta; Lee, Chen-An; Tang, Muoi; Chen, Yan-Ping
Graphical abstract: Highlights: Novel solubility data of pyridin-4-amine in supercritical CO2 are reported. The measured solid solubility dare are satisfactorily correlated. The RESS experimental results for pyridin-4-amine are reported. Pyridin-4-amine is micronized to nearly spherical nanoparticles. Better dissolution profile is reported for RESS treated pyridin-4-amine. Abstract: Novel solute solubility data of pyridin-4-amine (C5 H6 N2, also known as 4-aminopyridine or fampridine) in supercritical carbon dioxide are measured in this study. This compound is an active pharmaceutical ingredient (API) for the treatment of neurological disorder, and the Alzheimer's disease. The solubility data at three isotherms (308.2, 318.2 and 328.2 K) are reported for pressures from 10 to 22 MPa. These solubility results are ranged from 2 × 10 −5 to 2 × 10 −4  mol fraction, and are confirmed as thermodynamically consistent. We further apply the rapid expansion of supercritical solution (RESS) process to micronize this API. At our optimal operation condition, the original API with a mean particle size of 532.3 ± 236.5 μm is micronized to 0.32 ± 0.07 μm. The RESS processed products are much more uniform and nearly spherical amorphous particles. Finally, an in vitro dissolution test illustrates an enhanced dissolution rate by 2.9 times for the micronized pyridin-4-amine.